FAT AND WATER CONTENTS OF THE MUSCLE AND OVARY DURING THE MATURATION CYCLE OF PSEUDOSCIAENA ANEUS (BLOCK) AND JOHNIUS CARUTTA (BLOCH) - Rao, T Appa (Indian Journal of Fisheries, 2011)
In fishes fat accumulates mostly in muscles, liver, intestine and gonads for utilization during the reproductive activity (Milroy, 1898; Bruce, 1924; Channon and Saby, 1932; Lovern and Wood, 1937; Hickling, 1947; Bailey, 1952; Hoar, 1957; Love, 1957). Previous investigations (Milroy, 1898; Lovern and Wood, 1937; Hickling, 1947) revealed that during maturation the fats which are stored in various organs are transferred to maturing gonads. Durairaj (1962) reviewed some previous investigations made with reference to nutritive value and seasonal variations in fat contents of the fishes in India.’ The present problem was taken up during the period of 1961-62 with a view to studying the quantitative distribution of fat and water in flesh and ovaries in diflferent stages of maturity of Pseudosciaena aneus and Johnius carut